Konstruksi Hukum Terhadap Penetapan Bunga Tinggi pada Investasi yang Diselenggarakan Koperasi Simpan Pinjam - Yeti Sumiyati; Ratna Januarita; Tatty A Ramli; Efik Yusdiansyah (University of Udayana, 2021)
The purpose of this research is to examine the adequacy of laws and regulations governing investment implementation by the Savings and Credit Cooperative (KSP) and formulate legal constructs related to the determination of investment interest rates by KSP through the regulations of the Indonesian Deposit Insurance Corporation (IDIC/LPS) concerning the Determination of the Deposit Insurance Interest Rate in the form of IDIC Regulation (Surat Edaran). The research method uses a normative juridical approach, descriptive-analytical research specifications, the systematic interpretation and the legal construction of analogy. The results showed that the statutory regulations governing investments made by KSP were insufficient, especially in the section relating to the determination of investment interest rates. There were still many KSPs that set high interest in their investment programs. Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 7 of 2021 concerning Ease, Protection, and Empowerment of Cooperatives and Micro, Small and Medium Enterprises also does not accommodate provisions regarding investment programs that KSP can carry out. It is feared that several new provisions in the two regulations will lead to high-interest investment practices by KSP that prioritize the interests of their institutions over the welfare of members. Through the analysis of legal construction, it was found that the IDIC Regulation (Surat Edaran) regarding the Determination of the Deposit Insurance Interest Rate at Commercial Banks and Rural Banks can be used as a reference by the Ministry of Cooperatives and SMEs to encourage KSP to set investment interest rates fairly. Tujuan penelitian ini adalah untuk mengkaji kecukupan peraturan perundang-undangan yang mengatur tentang penyelenggaraan investasi oleh Koperasi Simpan Pinjam (KSP) dan merumuskan konstruksi hukum terkait penetapan suku bunga investasi oleh KSP melalui peraturan Lembaga Penjamin Simpanan (LPS) tentang Penetapan Tingkat Bunga Penjaminan Simpanan dalam bentuk Surat Edaran LSP. Metode penelitian menggunakan pendekatan yuridis normatif, spesifikasi penelitian deskriptif analitis dan metode analisis data yang digunakan adalah penafsiran sistematis dan konstruksi hukum analogi. Hasil penelitian menunjukkan bahwa peraturan perundang-undangan yang mengatur mengenai investasi yang dilakukan KSP tidak cukup memadai khususnya pada bagian yang berkaitan dengan penetapan suku bunga investasi sehingga masih banyak KSP yang menetapkan bunga tinggi dalam program investasinya. Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja dan Peraturan Pemerintah Nomor 7 Tahun 2021 tentang Kemudahan, Perlindungan dan Pemberdayaan Koperasi dan Usaha Mikro Kecil dan Menengah, juga tidak mengakomodasi ketentuan tentang program investasi yang dapat dilakukan KSP. Beberapa ketentuan baru dalam kedua peraturan tersebut dikhawatirkan memunculkan banyak praktik investasi berbunga tinggi oleh KSP yang lebih mengutamakan kepentingan lembaganya dibandingkan kesejahteraan anggota. Melalui analisis konstruksi hukum, ditemukan bahwa Surat Edaran Lembaga Penjamin Simpanan (LPS) tentang Penetapan Tingkat Bunga Penjaminan Simpanan pada Bank Umum dan Bank Perkreditan Rakyat dapat dijadikan rujukan oleh Kementerian Koperasi dan UKM untuk mendorong KSP dalam menetapkan suku bunga investasi secara wajar